Morpholine Amides: Classical but Underexplored Acylating Intermediates in Organic Synthesis - Ogiwara, Yohei (Synthesis, 2025)
Morpholine amides are classical yet underexplored acylating agents in organic synthesis. Compared to other amides, such as Weinreb amides, morpholine amides offer distinct advantages such as high water solubility, economic accessibility, and operational stability. This review highlights recent advancements in the use of morpholine amides for the synthesis of ketones, aldehydes, and acylsilanes via selective mono-addition of organometallic or hydride reagents. Their applications in key steps of complex molecule synthesis, including natural product synthesis, Vilsmeier–Haack reactions, and polymer recycling processes, are also discussed. Particular attention is paid to the unique reactivity and chemoselectivity of morpholine amides that distinguish them from other amide derivatives, offering practical and scalable strategies in modern synthetic chemistry.
Keywords: Morpholine amide; Acylating agent; Mono-addition; Ketone synthesis; Weinreb alternative; Divergent building block; Hydride reduction